2009
DOI: 10.1097/qad.0b013e32831fb51a
|View full text |Cite
|
Sign up to set email alerts
|

Unprotected anal intercourse, risk reduction behaviours, and subsequent HIV infection in a cohort of homosexual men

Abstract: Objective-A range of risk reduction behaviours in which homosexual men practise unprotected anal intercourse (UAI) has been described. We aimed to assess the extent of any reduction in HIV risk associated with these behaviours.Design-A prospective cohort study of HIV-negative homosexual men in Sydney, Australia. Methods-Men were followed up with 6-monthly detailed behavioural interviews and annual testing for HIV. The four risk reduction behaviours (behaviourally defined) examined were serosorting, negotiated … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
203
0

Year Published

2009
2009
2019
2019

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 214 publications
(206 citation statements)
references
References 35 publications
3
203
0
Order By: Relevance
“…20 Although recent ground breaking randomized clinical trials have demonstrated that antiretroviral therapy (ART) decreases rates of HIV seroconversion and onward transmission, substance users were excluded from these well-controlled efficacy trials. 21,22 Further clinical research is needed to examine whether behavioral interventions targeting substance use and sexual risk behavior optimize the effectiveness of ART for HIV prevention with substance-using MSM.…”
Section: Substance Use and Hiv/aids 949mentioning
confidence: 99%
See 1 more Smart Citation
“…20 Although recent ground breaking randomized clinical trials have demonstrated that antiretroviral therapy (ART) decreases rates of HIV seroconversion and onward transmission, substance users were excluded from these well-controlled efficacy trials. 21,22 Further clinical research is needed to examine whether behavioral interventions targeting substance use and sexual risk behavior optimize the effectiveness of ART for HIV prevention with substance-using MSM.…”
Section: Substance Use and Hiv/aids 949mentioning
confidence: 99%
“…Compared to a reference group that reported no UAI (n=415), separate multivariate logistic regression analyses examined correlates of SDUAI (n=105) and serosorting among HIV-negative MSM (n=185). 20 The multivariate models included interaction terms for sexual compulsivity with stimulant, poppers, EDM, and alcohol use. Stratified AORs adjusted for variables that were significant in the full multivariate model (e.g., poppers, EDM use), were calculated to probe significant interaction terms.…”
Section: Methodsmentioning
confidence: 99%
“…12,23 Serosorting has become much more commonly practised by GBM in the last decade, 12,40 but it is does not protect HIVnegative men if HIV status is incorrectly assumed or a partner has undiagnosed HIV. 24,41,42 In fact, the greater reliance on serosorting may have increased the exposure of HIV-negative men to undiagnosed HIV, which may explain why other positive changes (such as the increase in HIV treatment and undetectable viral load) have had limited effect. 12,37 Based on current trends, we expect CAI between casual partners to become more common over time and for HIV notifications to continue to rise if additional protective strategies are not deployed.…”
Section: Discussionmentioning
confidence: 99%
“…24 This classification system can be stratified by HIV status, reporting categories 1-2, 4 and 6-7 for HIV-negative and untested men and categories 1-3 and 5 for HIV-positive men only.…”
Section: Methodsmentioning
confidence: 99%
“…where both partners are HIV-negative), negotiated safety agreements, where the couple agrees not to have CLAI with outside partners, are associated with a low HIV incidence. 24 Use of negotiated safety has been common in Australia since the mid-1990s, 25 and HIV testing rates are comparatively high. 26 This may explain, in part, the lower proportion of infections ascribed to romantic, committed relationships compared with elsewhere.…”
Section: Introductionmentioning
confidence: 99%